MODERN APPROACHES TO THE STUDY OF INTERNATIONAL RELATIONS OF CENTRAL ASIA WITH EUROPE - Izzatilla M. Khaydarov; Sh. E. Ziyoyev (Modern American Journals, 2025)
This article is devoted to the participation of Central Asian states in international processes and the place of Europe in them. In the article, the authors, responding to concepts widely used by the scientific community, various interdisciplinary theories and views, try to reveal the impact of the region on its relations with Western countries, including Europe. The work also analyzes the tendency of the region to engage in external (extra-regional) processes in the modern era from a historical perspective and based on an interdisciplinary approach. The priorities, mutual problems and solutions in the relations of Central Asian states with Europe from the post-independence period to the present are also put forward.
Keywords: Central Asia, interregional relations